ASSESSING CARPAL TUNNEL SYNDROME AMONG ADMINISTRATIVE STAFF OF A HIGHER LEARNING INSTITUTION: A PRELIMINARY STUDY - Muhammad Kamil Che Hasan; Muhammad Shazwan Azman; Zulkhairul Naim Bin Sidek Ahmad; Farrah Ilyani Che Jamaludin; Mohd Khairul Zul Hasymi Firdaus (Belitung Raya Foundation, Indonesia, 2020)
Background: Repeated hand and wrist movements increase the risk of carpal tunnel syndrome (CTS). The administrative staff is one of the high-risk classes that repeatedly involve the execution of identical tasks. Objective: This preliminary study was conducted to determine the prevalence of CTS among administrative staff and identify the socio-demographic and occupational risk factors for this syndrome. Methods: Descriptive cross-sectional study design was conducted amongst administrative staff at one of the higher learning institutions in Pahang, Malaysia. A total of 61 respondents were conveniently sampled according to the inclusion criteria. Respondents were required to undergo three tests (Phallen’s test, Thinel’s test, Durkan’s test) to identify probable CTS and answer questionnaires (socio-demographic background, occupational risk factors, and Boston Carpal Tunnel Syndrome Questionnaire). Data were analyzed using SPSS, and a Chi-square test was used to identify risk factors for CTS. Results: The average age for respondents was 31.72 (+5.38). The majority of respondents were female (70.5%), with a bachelor’s degree background and below (91.2%), and never used ergonomic tools (68.9%). The prevalence of probable CTS was 16.5% (n=10). There is no statistically significant finding between socio-demographic and occupational risk factors with probable CTS (p >.05). Conclusion: The data from this preliminary study revealed no association between the use of computers at work and probable CTS in a higher learning institution. Although the findings are not significant, this study can be used as a baseline for a future longitudinal study for nurses and other healthcare professionals to encourage good occupational and environmental health.